Circular Economy for Transport Infrastructure: An Overview of the Sustainable Use of Recycled Asphalt Shingles in Asphalt Mixtures - Marco Pasetto; Safeer Haider; Emiliano Pasquini (Applied Sciences)
In North America and Europe, asphalt shingle waste created during the installation of roofing membranes and tear-off shingles retrieved at the end of the membrane’s life cycle are two major sources of municipal solid waste. Since almost 15–35% of recycled asphalt shingles (RAS) consist of an asphalt binder, the effective recycling of RAS into asphalt mixtures could also allow a reduction in the consumption of non-renewable resources such as asphalt binders. In this context, several studies investigating the use of RAS in asphalt mixtures can be found in the literature, although they exhibit widespread and sometimes conflicting information about the investigated materials, the mix preparation and testing methodologies and the experimental findings. Given this background, this review paper aims at summarizing the existing information and research gaps, providing a synthetic and rational picture of the current literature, where similar attempts cannot be found. In particular, different research studies show that the use of RAS in asphalt mixtures is an economical as well as an eco-friendly option. RAS with up to 20% by weight of binder or 5% by weight of aggregate/mixtures (eventually in combination with 15% reclaimed asphalt pavement aggregate) were found to be relatively suitable to improve the performance properties of asphalt mixtures, both in the laboratory and in the field. Adding RAS to asphalt mixtures could enhance their stiffness, strength and rutting resistance (i.e., high-temperature properties), while negatively affecting the mixtures’ fatigue and thermal cracking resistance. However, the addition of specific biomaterials (e.g., bio-binders, bio-oils) or additives to asphalt mixtures can mitigate such issues, resulting in lower brittleness and shear susceptibilities and thus improving the anti-cracking performance. On the other hand, the literature review revealed that several aspects still need to be studied in detail. As an example, RAS-modified porous asphalt mixtures (fatigue, rutting, moisture susceptibility and thermal cracking) need specific research, and there are no comprehensive research studies on the effects of the RAS mixing time, size and mixing temperature in asphalt mixtures. Moreover, the addition of waste cooking/engine oils (biomaterials) as asphalt binder rejuvenators in combination with RAS represents an attractive aspect to be studied in detail.